Gerakan Edukatif Bermain LEGO BRICK untuk Optimalisasi Motorik Halus Anak Usia Sekolah Dasar - Asri Putri Anugraini; Shinta Masitho Windriyani; Ary Artanty; Paulus Rah Adi Pawitra; Sari Mellina Tobing (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
The development of fine motor skills in elementary school-aged children is crucial for academic achievement and daily activities. However, some children still experience delays in fine motor skills due to lack of stimulation, a lack of varied teaching methods, and the impact of technology use and learning after the pandemic. This study aims to improve fine motor skills in elementary school children through Educational Activities Using LEGO Bricks. The method used is a play-based learning approach integrated into thematic learning. The activities were conducted in several structured sessions, including an introduction, core activities, and reflection and evaluation. Participants were elementary school students who actively participated in LEGO assembly activities both individually and in groups. The results showed improvements in fine motor skills, evident in improvements in hand-eye coordination, accuracy, concentration, and manipulative abilities. Students also demonstrated great enthusiasm and progress in creativity when creating various types of works. The discussion indicates that playing with LEGO is beneficial for training small muscles in the hands through pinching, pressing, and arranging activities, as well as supporting cognitive development and a passion for learning. In other words, the LEGO Brick Educational Play Movement has proven to be an innovative and fun learning medium, as well as effective in developing the fine motor skills of elementary school students.